Association of body mass index with 30-day all-cause mortality in cardiogenic shock - Schmitt, Alexander; Schupp, Tobias; Rusnak, Jonas; Weidner, Kathrin; Ruka, Marinela; Egner-Walter, Sascha; Mashayekhi, Kambis; Tajti, Péter; Ayoub, Mohamed; Behnes, Michael; Akın, Ibrahim (Nutrition, metabolism and cardiovascular diseases, 2024)
Background and Aims - This study investigates the prognostic impact of body mass index (BMI) on the risk of 30-day all-cause mortality in patients with cardiogenic shock (CS). Due to ongoing epidemiological developments, the characteristics of patients with cardiovascular disease are consistently changing. Especially increasing rates of obesity and associated comorbidities have been observed. However, data regarding the prognostic value of BMI in patients with CS remains inconclusive. - Methods and Results - Consecutive patients with CS were included from 2019 to 2021. The prognostic value of BMI (i.e., BMI 18.5-<25; 25-30 and >30 kg/m2) was analyzed using Kaplan-Meier and multivariable Cox proportional regression analyses regarding the primary endpoint of 30-day all-cause mortality. Additional risk stratification was performed based on the presence or absence of CS related to acute myocardial infarction (AMI). 256 patients with a median BMI of 26.4 kg/m2 were included. The overall risk of 30-day all-cause mortality was 53.5%. Within the entire study cohort, BMI was not associated with the risk of 30-day all-cause mortality (log rank p ≥ 0.107). In contrast, BMI >30 kg/m2 was associated with higher risk of 30-day all-cause mortality when compared to BMI <25 kg/m2 in patients with AMI-CS (78% vs 47%; log rank p = 0.017), which was confirmed after multivariable adjustment (HR = 2.466; 95% CI 1.126-5.399; p = 0.024). However, BMI was not associated with mortality in patients with non-AMI-CS. - Conclusion - BMI >30 kg/m2 was associated with increased risk of 30-day all-cause mortality in patients with AMI-CS, but not in non-AMI-CS.
Gesehen am 11.03.2025